2010
DOI: 10.1111/j.1365-2648.2010.05328.x
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual health, clinical practice stress, depressive tendency and health‐promoting behaviours among nursing students

Abstract: These results are consistent with research findings from western countries. Educators should develop strategies to address nursing students' spiritual health. This may help nursing students to manage their stress, to reduce depressive symptoms and to enhance health-promoting behaviours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
62
3
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 40 publications
(48 reference statements)
10
62
3
2
Order By: Relevance
“…In view of this, it appears that having religious beliefs enables rehabilitation experts to consider helping patients as a way of finding the meaning of life and gaining a higher job satisfaction. This finding was consistent with previous studies [3,4,[23][24][25][26][27][28].…”
Section: Discussionsupporting
confidence: 83%
“…In view of this, it appears that having religious beliefs enables rehabilitation experts to consider helping patients as a way of finding the meaning of life and gaining a higher job satisfaction. This finding was consistent with previous studies [3,4,[23][24][25][26][27][28].…”
Section: Discussionsupporting
confidence: 83%
“…Thus, they might feel more stress than other students or people in general. Medical students in other countries also showed a high prevalence of IBS, e.g., 15.8% in Malaysia [19], 26.0% in Pakistan [20], and 26.1% in Nigeria [21]. Tan et al [19] studied Malaysian medical students and reported that students with IBS felt more anxiety and depression (p = 0.002, p = 0.002).…”
Section: Discussionmentioning
confidence: 94%
“…One of the reasons for this difference was that the subjects were nursing and medical school students, who worked irregular hours because of their studies and practice schedules. Some studies have shown [15,16] that there are a variety of stressors in clinical practice. Jimenez et al [17] identified three types of stressors (clinical, academic, and external) and two categories of symptoms (physiological and psychological) linked to clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Nursing has been considered stressful due to the particularities of its work process. 4 However, some studies have shown that the professional training of nurses has been identified as stressful by university students, [5][6][7] who have to administer personal and social life, the requirements of the university where they study and the preparation for their professional career. 8 In addition, the transition from academic to professional life is a period that involves important personal decisions such as where and when to start the professional career and when to start a family and assume financial responsibilities.…”
Section: Introductionmentioning
confidence: 99%